Mutual Benefit Principle As Bilateral Basis of Indonesia With Thailand And Taiwan - Kadarudin; Thamrin, Husni; Liao, I-Ming; Satalak, Pataramon (International Journal of Global Community, 2019)
Mutual Benefit Principle in relations between countries requires that the subjects of international law (especially the state) in carrying out international relations be based on good faith so as to benefit all parties. Mutual benefit principle requires equal rights, namely that all parties strive to be mutually beneficial to each other, initially this principle is used to accommodate the nature and purpose of the business. But along with the times and to meet needs that are already cross-country, then this principle can be used as a reference in international relations, especially bilateral relations between the two countries, although this principle is also in accordance with the context of multilateral relations between many countries. This principle is used by Indonesia and Thailand in the cooperation of two countries that have been officially carried out since 1947, as well as Indonesia and Taiwan since 1971, on the basis of this principle, so far, the relationship between Indonesia and Thailand and Taiwan is still well maintained and running, and benefit each country.